2008
DOI: 10.1590/s0074-02762008005000012
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia maruaga (Diptera: Psychodidae), a new bat-cave sand fly from Amazonas, Brazil

Abstract: A new species of parthenogenetic, autogenic and apparently extremely endemic phlebotomine is described from a sandstone cave located in primary terra firme forest to the North of the city of Manaus. Specimens The caves and other arenitic formations of the municipal district of Presidente Figueiredo are singular relicts of the Palaeozoic (Karmann 1986), surviving between the more recent Amazonian sediments and the ancient rocks of the Guiana Shield. As part of a biological inventory of the area, insects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…Several recent studies have contributed to the knowledge of the biodiversity of Brazilian caves. Alves et al (2008) described Lutzomyia maruaga, which was captured in the aphotic zone of a sandstone cave in AM. Carvalho et al (2010) described Martinsmyia reginae, captured in a cave in the state of Tocantins, and Carvalho et al (2011a) described Evandromyia spelunca, found in a cave in Lassance, MG.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have contributed to the knowledge of the biodiversity of Brazilian caves. Alves et al (2008) described Lutzomyia maruaga, which was captured in the aphotic zone of a sandstone cave in AM. Carvalho et al (2010) described Martinsmyia reginae, captured in a cave in the state of Tocantins, and Carvalho et al (2011a) described Evandromyia spelunca, found in a cave in Lassance, MG.…”
Section: Discussionmentioning
confidence: 99%
“…All captured specimens were identified after clarification process (Young & Duncan 1994). For Deanemyia maruaga, other techniques were used to clarify and are discussed in Alves et al (2008), as well as a description of the biology of adults.…”
Section: Methodsmentioning
confidence: 99%
“…It is probable that some of them use the caves as resting places, as in the case of those of Brumptomyia and Psathyromyia, closely associated with armadillo burrows (Forattini 1973;Young & Duncan 1994), as well as Migonemyia, Nyssomyia, Psychodopygus, Trichophoromyia and some species of Pintomyia and Psathyromyia that are associated with forests (Aguiar & Medeiros 2003). Some species are troglophiles (Galati et al 2003a) and the endemic, parthenogenetic and autogenic Deanemyia maruaga (Alves, Freitas & Barret, 2008) (Alves et al 2008) can be identified as a troglobite species.…”
mentioning
confidence: 99%